The Effectiveness of Word Search Puzzles Game in Improving Student's Vocabulary - Tira Nur Fitria (Pioneer: Journal of Language and Literature, 2023)
With the growing popularity of the Word Search Puzzles game in educational contexts, teaching today aims to demonstrate the positive effects of Word Search Puzzles in teaching. This study reviews the effectiveness of Word Search Puzzles in improving students’ vocabulary. The method used in this research using a systematic literature review. The findings show that from 30 article journals have been found, 12 journals can be used as secondary data because meet the requirements which are then analyzed and summarized. These data qualify with QA1 (journal published in recent 7 years between 2015-2022), QA2 (research focus on the use of Word Search Puzzle for Indonesian students), QA3 (findings explain the improvement of students’ vocabulary using crossword puzzles), and QA4 (findings compare the improvement of two different classes between control and experiment class). The experimental class is the class that gets treatment (using Word Search Puzzle), while the control class is the group that does not get treatment (non-crossword puzzle). After the teacher teach vocabulary using the media “Word Search Puzzle, there is an improvement score from previous research in the pretest and posttest, especially in the experiment class taught by using Word Search Puzzle.